Integrasi Inovasi Herbal dan Aktivitas Fisik : Model Pengabdian Masyarakat untuk Mengelola Diabetes Melitus - N Sukesi; R Winarti (PPNI UNIMMAN, 2025)
Diabetes mellitus continues to be an alarming health challenge, especially in the context of public health, where there are so many cases of diabetes mellitus that patients do not know how to manage and prevent it. The aim of this community service program is to integrate local community empowerment with herbal innovations, especially clitoria ternatea and diabetic foot exercises as a holistic way to manage blood glucose levels. The program was delivered in RW XIII of Beringin village, Ngaliyan sub-district and included health education components and training sessions, including the production of herbal products. The initiative changed participants' knowledge and attitudes towards diabetes and enabled them to take control of managing their condition. This model proves that combining traditional herbal innovations with physical activity at the community level can effectively prevent and help manage diabetes mellitus at minimal cost.